Adversarial Robustness of Claude-3.5-Sonnet and Quantized Mobile Models in MobileAloha Tasks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 16 peer-reviewed papers addressing the following research question: How robust are instruction-following capabilities of Claude-3.5-Sonnet and quantized mobile models when tested with adversarial perturbations in the MobileAloha dataset, measured by success rate and. 16 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.2/10. This report
Machine-generated literature synthesis.